Socio-Cultural Issues in To Kill Mockingbird by Harper Lee - HADJ SAD, Mebarka (University of El-oued, 2022)
To kill a Mockingbird is a novel that tackles the challenging issues of race, rape, education, religion and innocence through the eyes of a little girl named Scout. Thus, the current study attempts to conduct a thematic analysis to investigate the socio-cultural issues in Harper Lee's novel To Kill a Mockingbird. In order to conduct this study, three questions have been asked. The first inquires the ways of the representation of the social issues in To Kill a Mockingbird. The second seeks to the way of the exemplification of the cultural issues in the novel. The third examines the extent of compatibility between the socio-cultural issues in the novel and real life of Americans at the novel time. To respond to the previously asked questions, three hypotheses have been formulated; the first seeks to highlight that the social issues in To Kill a Mockingbird are social class, gender roles and stereotypes, racism against African American, and justice and equality. The second hypothesize is that the cultural issues in the novel are education, religion, and struggle with identity. The third examines that Lee's portrays reflect the real image of the socio-cultural issues in early twentieth century. Accordingly, the study revealed the following results; social and cultural issues have been extensively used in the novel. To Kill a Mockingbird were concerning the causes and consequences of racism and prejudice, as well as how good and evil can coexist within a single community or individual religion and education. Thus social and cultural issues were justified and presented in different features. In addition, Lee's portrayal reflects the real images of American socio-cultural issues.
Keywords: Great Depression, Cultural issues; Social issues, To Kill a Mockingbird